Development of Flipbook-Based Learning Media Using the Dick & Carey Model and Its Impact on Elementary School Students’ Creative Problem-Solving Skills - Yasni, Zainul; Djono; Maulidina, Rizqiya C Wanda; Santoso, Fatan Alim; Agustin, Ika Wahyu (Indonesian Journal of Learning and Instructional Innovation, 2025)
The development of educational technology encourages the use of interactive digital media capable of delivering multimodal and adaptive learning. This study aims to develop Flipbook Maker-based learning media with the Dick & Carey instructional design model and analysed its effectiveness in improving elementary school students' problem-solving creativity. The development was carried out through the stages of needs analysis, design, production, formative evaluation, revision, and summative evaluation. This study used a modified Research and Development (R&D) approach involving expert validation, individual trials, small group trials, and field tests. The problem-solving creativity instrument was compiled based on indicators of fluency, flexibility, originality, and elaboration. The results showed that the flipbook obtained a "very valid" category from the validators of materials, media, and learning design. The field trial showed that the media was easy to use, interesting, and increased student learning engagement. Pretest-post-test analysis showed a significant increase in all indicators of problem-solving creativity (p < .001), with a large effect size (d = 1.21). These findings confirm that flipbooks developed systematically and based on multimedia theory are able to support creative thinking processes effectively, making them relevant for use in 21st-century learning.